2017
DOI: 10.1016/j.tra.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Information for travelling: Awareness and usage of the various sources of information available to public transport users in NSW

Abstract: Public transport authorities and service providers place great emphasis on information provision to travellers both before and during travel. Information provided prior to travel has included brochures, printed timetables, newspaper advertisements, telephone services and marketing campaigns. During the trip, providers have tended to use maps at public transport stops (i.e. bus stops, train stations, ferry wharves, etc.) as well as timetables both static and dynamic or real-time. Some of these channels are stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 28 publications
(13 reference statements)
4
19
0
Order By: Relevance
“…no smartphone) 905 greater for respondents who reported < 1 trip per week as opposed to those who reported 5 + trips per week. This is consistent with other studies that have shown that differences exist between passengers making frequent versus infrequent trips (Mulley et al 2017). Among all the socio-demographic variables considered, the employment status variable had a significant effect on pre-travel information-seeking behaviour.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…no smartphone) 905 greater for respondents who reported < 1 trip per week as opposed to those who reported 5 + trips per week. This is consistent with other studies that have shown that differences exist between passengers making frequent versus infrequent trips (Mulley et al 2017). Among all the socio-demographic variables considered, the employment status variable had a significant effect on pre-travel information-seeking behaviour.…”
supporting
confidence: 91%
“…The model results suggest that trip context (specifically, all journey planning stages except for plan at station/stop/on-board) and preferred mode have a significant effect on pre-travel information-seeking behaviour. This finding provides further support to Mulley et al (2017), who suggested that public transport users do identify a variety of information needs at different stages of their journey. The odds of searching for pre-travel public transport information are 0.553 times less for respondents with a smartphone who typically plan their journeys at locations other than at home/work/station/stop/on-board (for example, while travelling to their next mode of transport or undertaking other activities) as opposed to those with a smartphone who typically plan their journeys at home/work.…”
Section: Effect Of Trip Context and Preferred Mode Of Public Transporsupporting
confidence: 76%
See 1 more Smart Citation
“…Some policies, such as those of land use and transport planning [18,19], incentives to public transport, and information campaigns [20], can be combined with corrective instruments. In addition, regulations or new technology could play a role [5].…”
Section: Introductionmentioning
confidence: 99%
“…1 In the literature, these electronic passenger information systems containing real-time (travel) information-RT(T)I-are sometimes termed advanced public transport (or transit) traveller information systems-A(P) TTIS (Nuzzolo et al 2015). They can be based on site-specific equipment (signs and displays on vehicles and at stops and stations) or on personal devices such as smartphones and personal computers (Fonzone 2015;Ghahramani and Brakewood 2016;Harmony and Gayah 2017;Mulley et al 2017). The information content on stationary or vehicle-based displays usually comprises scheduled and actual departure times, while journey planners and the like, available through personal devices, also to an increasing degree include itineraries with updated departure and arrival times of connecting services at transfer points (for example, as described by Cats et al 2016).…”
Section: Introductionmentioning
confidence: 99%